Persepsi Mahasiswa Fakultas Ekonomi Universitas Negeri Medan Terhadap Pemilahan Sampah di Lingkungan Kampus - Tri Rahayu; Mutia Anissa; Nakita Nakita; Ranti Delima Tobing; Bonaraja Purba (CV. Ulil Albab Corp, 2024)
This study aims to analyze the perceptions of students at the Faculty of Economics, Universitas Negeri Medan, regarding waste sorting on campus. Utilizing a quantitative research method, data were collected through a structured questionnaire distributed via social media, targeting a sample of 50 active students. The findings reveal that a significant portion of students lacks awareness and understanding of proper waste sorting practices, with only 40% acknowledging the adequacy of waste disposal facilities on campus. The results indicate that the current waste management program is insufficiently supported by student engagement, which is crucial for its success. Furthermore, the study highlights the need for enhanced educational initiatives to foster a culture of environmental responsibility among students. In conclusion, the research underscores the importance of improving waste management strategies in higher education institutions to promote sustainable practices and contribute to broader environmental goals in Indonesia. This study not only provides insights for decision-makers at Universitas Negeri Medan but also adds to the existing literature on pro-environmental behavior in the Indonesian socio-cultural context.